THE STATE OF DEVELOPMENT OF TEXTILE INDUSTRY ENTERPRISES IN UZBEKISTAN - Gulnozakhon Muydinova (American Journals, 2023)
Light industry, being a strategic sector not only for the economy of Uzbekistan, but also for all countries of the world, provides a high level of employment, helps strengthen the economic and industrial potential and international prestige of our country. Light industry is developing every year. The introduction of new production technologies, the use of high-performance, modern equipment and at the same time effective management ensure high labor productivity and an increase in industrial production volumes. The republic, which for many years exported only cotton fiber, today has unlimited opportunities to take a leading position in the global textile market not only as a supplier of cotton fiber, but also as an exporter of textile products, especially finished products.
Keywords: Light industry, textile industry, textile products, textile market, export, clothing and knitwear products.